Causal associations between sleep traits and temporomandibular disorders: a bidirectional mendelian randomization analysis - Xu, Lihan; Zhou, Haojing (Frontiers in Genetics, 2024)
Objectives: This study aims to investigate the relationship between five sleep traits (insomnia, sleep duration, getting up in morning, snoring, and daytime nap) and temporomandibular disorders (TMD) using bi-directional Mendelian randomization.The bi-directional Mendelian randomization study was conducted in two stages.Initially, sleep traits were examined as exposures while TMD was evaluated as an outcome, whereas the second step was reversed. The inverse variance weighted (IVW) method and other Mendelian randomization methods were used for analysis. Furthermore, we performed the MR-Egger intercept, MR-PRESSO, Cochran's Q test, and "Leave-one-out" to assess the levels of pleiotropy and heterogeneity.The IVW method indicates that getting up in the morning reduces the risk of developing TMD (OR = 0.50, 95% CI 0.30-0.81, P = 0.005), while insomnia may increase the risk of TMD (OR = 2.05, 95% CI 1.10-3.85, P = 0.025). However, other sleep traits are not associated with the risk of TMD, and having TMD does not alter an individual's sleep traits. After removing outliers, the results remained robust, with no pleiotropy detected.Conclusions: Genetically determined difficulty in getting up in the morning and insomnia can increase the risk of TMD. By optimizing sleep, the risk of developing TMD can be reduced. This underscores the importance of sleep in preventing TMD.